A Study Of Generating Abstract Test For Requirement Validation Among Requirement Engineers - Moketar, Nor Aiza; Kamalrudin, Massila; Mohd Yusof, Mokhtar; Sidek, Safiah; Robinson, Mark (JATIT & LLS, 2017)
Requirements testing or requirements-based testing (RBT) is one of the software testing techniques that is found effective to test requirements’ completeness and accuracy. This technique involves systematic way of test case generation from the model of the requirements specification. This technique has been applied in the requirements analysis phase to detect and eliminate requirements defects before the next stage of software development project. Although this technique is useful, it is tedious and time consuming to manually generate abstract test from the requirements model. However, we argue that the tedious process can be minimised if the requirements engineer have the good ability (skill) to generate abstract test from requirements models for requirements validation. This paper described a study of requirements engineer manually generate abstract tests from requirements model: Essential Use Cases (EUC) model. From the result, we discover that software requirements engineers are not well equipped with the skill and technique to generate abstract tests from requirements model.